Karakteristik Penderita Kanker Serviks yang Dirawat Inap di RSUD Arifin Achmad Pekanbaru Tahun 2011-2013 - Khairun Nikmah Hasibuan; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT Cervical cancer is one of malignant disease in women, especially in developing countries, including Indonesia. Hospital Information System data in 2007 there were 11.78% of cervical cancer patients who were admitted to hospital in Indonesian and more than 70% of patients present in an advanced stage. The characteristics of a patient that suffer from sevic cancer that are treated on RSUD Arifin Achmad Hospital in Pekanbaru years 2011-2013, descriptive study design Case series. This research population is 110 and all of these are samples, the analysis of data with Chi-Square, Fisher's Exact and Mann Whitney. The highest proportion of sociodemographic : age >35 years 90.9%, Malay 44.6%, Muslim 89.1%, 47.3% primary school education, Housewife 84.5% , 95.5% marital status and living outside Pekanbaru (69.1%). The main complaint of vaginal bleeding 57.3%, Multipara parity 51.8%, advanced clinical stage 85.5%, 53.6% radiotherapy medical management, not own cost 87.3%, long maintainability average 5.26 days and outpatient return 67.3 %. There are differences in the proportion of medical management based on clinical stage (p = 0.000). There is no difference between the proportions of age (p = 0.146), parity (p = 0.620), education (p = 0.161), marital status (p = 0.552) , the main complaint (p = 0.501), the source charge (p = 0.688), average long treatment (p = 0.817) based on clinical staging. Difference in the proportion of unknown clinical stage based on the circumstances at any home, the source of the cost based on the circumstances when home. Hospital and staff’s are advised to be more active in sharing any information based on cervical cancer, including early detection (Pap’s test/IVA) and moreover women should always be more cautions at any sign and symptoms also risk factors that can lead to cervical cancer. Key Words : Cervical Cancer, Characteristics.